P178 Carbon-Ion radiotherapy for malignant gynecological melanoma. (1st November 2019) - Barcellini, A; Vitolo, V; Lazzari, R; Consoli, F; Ditto, A; Facoetti, A; Fossati, P; Fiore, MR; Vischioni, B; Iannalfi, A; Laliscia, C; Mirandola, A; et al.
Abstract : Introduction/Background: We analyzed early clinical outcomes of carbon ion radiotherapy (CIRT) in the first patients with gynecological malignant mucosal melanoma(g-MMM) treated at CNAO. Methodology: Between 2016 and 2018, 9 patients(pts) with g-MMM were treated with CIRT after surgery or in exclusive settings (table 1) . They had 7 vaginal(VaM), 1 cervical(CM) and 1 vulvar(VuM)MMM. One pt with VaM had been previously irradiated with photons;8 pts are considered inoperable and 1 pt underwent adjuvant CIRT on the small pelvic space after radical surgery without lymphadenectomy. Two pts underwent neoadjuvant and sequential anti-PD-1 immunotherapy. Because of the large volume of macroscopic disease, CM and VuM patients were irradiated with up to a total dose of 28 GyRBE(3 fractions) and 68.8 GyRBE(16 fractions), respectively, to the Clinical Target Volume (CTV) defined as the Gross Tumor Volume (GTV)+uterine cervix and corpus for the CM and GTV+vulva for the VuM. For inoperable VaM, small pelvic space including GTV was irradiated with up to a total dose of 38.7-43 GyRBE followed by a GTV boost of up to a total dose of 68.8 GyRBE in 16 fractions (figure 1). All patients were treated with synchrotron-based scanning carbon ion beams. Early clinical and toxicity profile(according to CTCAE V4.03) were evaluated. Results: Treatment was well tolerated and no interruption was needed. For the evaluable pts, toxicity profile was favorable and no G≥2 acute/late toxicities were observed. Overall, for pts with a follow-up≥3 months, median LC ranged from 3 to 13 months( <for VuM and CM), median MFS and median OS was 6.5 (range: 3–23) and 9 months (range: 3–29.5) respectively. Data are still ongoing. Conclusion: Because of the high rate of distant metastasis and unsatisfactory survival benefit, a more conservative treatment approach, instead of extensive surgery, may be warranted. We think that CIRT may serve as a definitive treatment choice for patients with g-MMM. Disclosure: Nothing to disclose.